OPTIMALISASI FUNGSI LEMBAGA PENYIARAN PUBLIK KABUPATEN KUANTAN SINGINGI TAHUN 2016 - Fajri Akhmal Putra; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The background of this research is the formation of Kuansing FM radio as a medium of service and support the activities of local government, based on Kuantan Singingi Regent Regulation No. 7 of 2009 concerning Local Public Broadcasting Institution Kuansing FM. Kuansing FM Local Public Broadcasting Institution has been established since 2003 but in carrying out its function this radio has not been able to achieve the goal of the establishment of Kuansing FM radio. The non-optimal function of Kuansing FM radio is seen from several programs and activities of the 2016 Kuansing FM Local Public Broadcasting Institute which have not yet directly addressed the community such as the socialization program for public information disclosure, and rural broadcastsThis research directs how to optimize the function of FM Kuansing Local Public Broadcasting Institutions and the inhibiting factors that influence the non-optimal function of the Kuansing FM Local Public Broadcasting Institution. This study aims to describe the optimization of the functions of the Kuansing FM Local Public Broadcasting Institution and determine the inhibiting factors that influence the non-optimal functioning of the Local Public Broadcasting Institution Kuansing FM in 2016. This research is a qualitative approach research, this research was conducted in Kuantan Singingi District, the technique used to collect data in this study are interviews and documentation.The results showed that the Kuansing FM Local Public Broadcasting Agency disseminated development information to the public through electronic media, in accordance with District Head Regulation number 7 of 2009, it was still unable to perform its functions optimally as an electronic media information provider in Kuantan Singingi Regency. The legal power of the Kuansing FM Local Public Broadcasting Institute is still weak and seems to be ignored, this is indicated by the absence of broadcasting permits. The inhibiting factors in the optimization of the function of the FM Kuansing Local Public Broadcasting Agency are the lack of broadcasting permits that must be possessed, the quality and quantity of HR owned, lack of training, and lack of facilities and infrastructure.Keywords:Optimization, Public Broadcasting Institutions